Optimization of loop-mediated isothermal amplification (LAMP) assay for robust visualization in SARS-CoV-2 and emerging variants diagnosis - Luo, Zhen; Ye, Chunhong; Xiao, Heng; Yin, Jialing; Liang, Yicong; Ruan, Zhihui; Luo, Danju; Gao, Daolong; Tan, Qiuping; Li, Yongkui; Zhang, Qiwei; Liu, Weiyong; et al. (Chemical engineering science, 2022)
[Display omitted] •The colorimetric LAMP tool is rapid (40 min) and sensitive (10 copies).•The LAMP assay can be stably performed in portable heating devices.•This LAMP assay acts matchable effectiveness to qPCR detection.•This POC test is optimal in the diagnosis of main SARS-CoV-2 variants. Loop-mediated isothermal amplification (LAMP) is widely used in detection of pathogenic microorganisms including SARS-CoV-2. However, the performance of LAMP assay needs further exploration in the emerging SARS-CoV-2 variants test. Here, we design serials of primers and select an optimal set for LAMP-based on SARS-CoV-2 N gene for a robust and visual assay in SARS-CoV-2 diagnosis. The limit of detectable template reaches 10 copies of N gene per 25 μL reaction at isothermal 58℃ within 40 min. Importantly, the primers for LAMP assay locate at 12 to 213 nt of N gene, a highly conservative region, which serves as a compatible test in emerging SARS-CoV-2 variants. Comparison to a commercial qPCR assay, this LAMP assay exerts the high viability in diagnosis of 41 clinical samples. Our study optimizes an advantageous LAMP assay for colorimetric detection of SARS-CoV-2 and emerging variants, which is hopeful to be a promising test in COVID-19 surveillance.